A comparison of accumulated and distributed reinforcement periods with children exhibiting escape‐maintained problem behavior. Issue 2 (14th August 2019) - Fulton, Caitlin J.; Tiger, Jeffrey H.; Meitzen, Hannah M.; Effertz, Hannah M.
Abstract : Differential reinforcement is a common treatment for escape‐maintained problem behavior in which compliance is reinforced on a fixed‐ratio (FR) 1 schedule with brief access to positive and/or negative reinforcement. Recent research suggests some individuals prefer to complete longer work requirements culminating in prolonged (i.e. accumulated) reinforcement periods relative to brief (i.e. distributed) periods, but prolonged work exposure may evoke problem behavior and prevent compliance from contacting reinforcement when treating escape‐maintained problem behavior. We exposed 3 children with escape‐maintained problem behavior to both distributed (FR 1 resulting in 30 s of reinforcement) and accumulated (FR 15 resulting in 7.5 min of reinforcement) arrangements to compare their efficacy in maintaining low levels of problem behavior. We then assessed participants' preferences for these conditions in a concurrent‐chains arrangement. Accumulated‐reinforcement arrangements did not occasion additional problem behavior, but rather resulted in consistently lower levels of problem behavior for 2 of 3 participants. Participants demonstrated idiosyncratic preferences.